Safety and Efficacy of Dihydroartemisinin-Piperaquine for Intermittent Preventive Treatment of Malaria in Pregnancy: A Systematic Review of Randomized Controlled Trials - Arief, Thendi Abdul; Pertiwi, Luthfiah; Budiarti, Niky; Da Costa, Yohanna Lawanda; Ambarsari, Paulina (Jurnal Kefarmasian Indonesia, 2025)
Preventing malaria in pregnant women is crucial, especially for the safety of both the mother and the baby, particularly in malaria-endemic areas. Dihydroartemisinin-Piperaquine (DHP) is one of the options for Intermittent Preventive Treatment in pregnancy (IPTp). Although several previous studies have assessed DHP as a preventive antimalarial in pregnancy, this study systematically consolidates the most recent Randomized Controlled Trials (RCTs), reflecting new evidence and resistance trends to Sulfadoxine-Pyrimethamine (SP) across malaria-endemic regions. This study aims to review the safety and efficacy of DHP use during pregnancy. The methodology involved a comprehensive literature search from the databases PubMed, ScienceDirect, Google Scholar, and Cochrane, published in English from 2020 to 2024. Inclusion criteria encompassed double-blind RCT evaluating the use of DHP during pregnancy. Exclusion criteria included studies that did not involve pregnant women, did not use DHP, and study designs other than double-blind RCT. The initial search yielded 255 articles. After screening for duplicates, a total of 50 duplicates were removed. Ultimately, 5 articles were identified after screening titles, abstracts, and full texts. The analysis results indicate that IPTp DHP is more effective in reducing the incidence of malaria compared to IPTp SP. However, IPTp SP is safer to use than IPTp DHP due to fewer adverse effects. The use of DHP may be considered for IPTp in cases of SP resistance. This review provides an updated synthesis of recent RCTs focusing on the comparative safety and efficacy of DHP versus SP in IPTp of malaria in pregnancy, highlighting recent evidence in the context of emerging SP resistance.